Grafologi Mahasiswa pada Praktikum Zoologi Vertebrata - Sri Maya; Rizki Amalia Nur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the relationship between graphology learning outcomes and practical learning outcomes for the Department of Biology Education students. The method used is a complete report of the Vertebrate Zoology practicum as a sample of student handwriting and then analyzed using a graphological assessment instrument. The results showed that the value of the correlation coefficient or rxy obtained was 0.769. This value means that the higher the analysis of graphology results, the higher the learning outcomes of the Vertebrate Zoology practicum for Biology Education Department students. In conclusion, there is a solid relationship between the analysis of graphology results and the Vertebrate Zoology practicum learning outcomes in the Department of Biology Education, Maros Muslim University. Keywords: Graphology, Learning Outcomes, Practicum